Changes in tourists' perception of well-being based on their use of emotion regulation strategies during vacation. Issue 5 (13th June 2018) - Gao, Jie; Kerstetter, Deborah L.; Mowen, Andrew J.; Hickerson, Benjamin
ABSTRACT: Based on the theoretical foundation of emotion regulation, this exploratory study aimed to examine changes in tourists' perceived well-being and to determine whether these changes were due to use of emotion regulation strategies (ERSs) during their vacation. This study used travel diaries to record tourists' use of ERSs on a daily basis, and also measured tourists' perceived well-being one day before and after their vacation. Results indicated that tourists had significantly higher perceptions of well-being after vacation, and those who used ERSs were more likely to indicate a higher sense of well-being after vacation. The results provide new insight into which aspects of tourists' subjective and psychological well-being can be boosted by taking vacations and how these aspects may be enhanced by using different ERSs.